The illustrated Jesus through the centuries - Pelikan, Jaroslav 1923-2006 (Yale Univ. Press, 1997)
Discusses how each age created Jesus in its own image. "Pelikan...has condensed the original text and enhanced the book with more than 200 new illustrations, most in color, that give a new dimension to his thooughts."--Jacket.
Rev. ed. of: Jesus through the centuries. 1985
Keywords: Jesucristo - Iconografía; Jesus Christus; Jesus Christ -- History of doctrines; Jesus Christ -- Influence; Beeldende kunsten; Beeldvorming; Christologie; Darstellung; Kunst; Malerei; Geschichte